Calorie Labeling Promotes Dietary Self-Control by Shifting the Temporal Dynamics of Health- and Taste-Attribute Integration in Overweight Individuals. (March 2018) - Lim, Seung-Lark; Penrod, Molly T.; Ha, Oh-Ryeong; Bruce, Jared M.; Bruce, Amanda S.
Understanding why people make unhealthy food choices and how to promote healthier choices is critical to prevent obesity. Unhealthy food choices may occur when individuals fail to consider health attributes as quickly as taste attributes in their decisions, and this bias may be modifiable by health-related external cues. One hundred seventy-eight participants performed a mouse-tracking food-choice task with and without calorie information. With the addition of calorie information, participants made healthier choices. Without calorie information, the initial integration of health attributes in overweight individuals' decisions was about 230 ms delayed relative to the taste attributes, but calorie labeling promoted healthier choices by speeding up the integration of health attributes during a food-choice task. Our study suggests that obesogenic choices are related to the relative speed with which taste and health attributes are integrated into the decision process and that this bias is modifiable by external health-related cues.